Hydrogen Desorption Properties of Bulk and Nanoconfined LiBH4-NaAlH4 - Javadian, P.; Sheppard, Drew; Buckley, C.; Jensen, T. (MDPI, 2016)
Nanoconfinement of 2LiBH4-NaAlH4 into a mesoporous carbon aerogel scaffold with a pore size, BET surface area and total pore volume of Dmax = 30 nm, SBET = 689 m2/g and Vtot = 1.21 mL/g, respectively is investigated. Nanoconfinement of 2LiBH4-NaAlH4 facilitates a reduction in the temperature of the hydrogen release by 132 °C, compared to that of bulk 2LiBH4-NaAlH4 and the onset of hydrogen release is below 100 °C. The reversible hydrogen storage capacity is also significantly improved for the nanoconfined sample, maintaining 83% of the initial hydrogen content after three cycles compared to 47% for that of the bulk sample. During nanoconfinement, LiBH4 and NaAlH4 reacts to form LiAlH4 and NaBH4 and the final dehydrogenation products, obtained at 481 °C are LiH, LiAl, AlB2 and Al. After rehydrogenation of the nanoconfined sample at T = 400 °C and p(H2) = 126 bar, amorphous NaBH4 is recovered along with unreacted LiH, AlB2 and Al and suggests that NaBH4 is the main compound that can reversibly release and uptake hydrogen.